Raw physical oceanography and ocean current velocity data from mooring AWI208-9 in the Weddell Sea, January 2019 – April 2022 - Mario Hoppmann; Markus A Janout; Jacob Allerholt; Carina Engicht; Rainer Graupner; Pedro Llanillo; Matthias Monsees; Gerd Rohardt; Stefanie Spiesecke; Karolin Thomisch; Olaf Boebel; Mario Hoppema (PANGAEA, 2024)
Time-series data of physical oceanography and ocean current velocity were obtained from mooring AWI208-9 in the northern Weddell Sea between January 2019 and April 2022 as part of the Hybrid Antarctic Float Observing System (HAFOS). The mooring was deployed during RV POLARSTERN expedition PS117, and recovered during PS129. The attached archive contains raw data files of two Seabird SBE37 MicroCATs (nominal depths: 797m, 4758m; sampling interval 2h), and one Nortek Aquadopp current meters (nominal depth: 794m; sampling interval 1h). The mooring also included a Develogic Sonovault (nominal depth: 294m; raw data not publicly available) for passive acoustic monitoring. Auxiliary information such as sensor calibration sheets, mooring diagrams, and schedule files are also provided, if applicable. The 797m MicroCAT did not record any data.
In: Hoppmann, Mario; Janout, Markus A: Collection of raw datasets from oceanographic moorings in the Weddell Sea, Antarctica, in 2019 - 2025 [dataset publication series]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.971906 (dataset in review)